Conserved Function of ACYL–ACYL CARRIER PROTEIN DESATURASE 5 on Seed Oil and Oleic Acid Biosynthesis between Arabidopsis thaliana and Brassica napus - Jin, Changyu; Li, Dong; Gao, Chenhao; Liu, Kaige; Qi, Shuanghui; Duan, Shaowei; Li, Zixiong; Gong, Jingyun; Wang, Jianjun; Hai, Jiangbo; Chen, Mingxun (Frontiers in Plant Science, 2017)
Previous studies have shown that several ACYL-ACYL CARRIER PROTEIN DESATURASE (AtAAD) members in Arabidopsis thaliana are responsible for oleic acid (C18:1) biosynthesis. Limited research has been conducted on another member, AtAAD5, and its paralog BnAAD5 in the closely related and commercially important plant, Brassica napus. Here, we found that AtAAD5 was predominantly and exclusively expressed in developing embryos at the whole seed developmental stages. The aad5 mutation caused a significant decrease in the amounts of oil and C18:1, and a considerable increase in the content of stearic acid (C18:0) in mature seeds, suggesting that AtAAD5 functioned as an important facilitator of seed oil biosynthesis. We also cloned the full-length coding sequence of BnAAD5-1 from the A3 subgenome of the B. napus inbred line L111. We showed that ectopic expression of BnAAD5-1 in the A. thaliana aad5-2 mutant fully complemented the phenotypes of the mutant, such as lower oil content and altered contents of C18:0 and C18:1. These results help us to better understand the functions of AAD members in A. thaliana and B. napus and provide a promising target for genetic manipulation of B. napus.